Adaptability Analysis of Four-Leg Hydraulic Support with Large Mining Height under Impact Dynamic Load - Dalong Wang; Xiaoteng Zeng; Guofa Wang; Ran Li (Shock and Vibration)
In order to comprehensively analyze the adaptability of four-leg hydraulic support with large mining height under impact dynamic load, this paper adopts HyperMesh software to conduct a flexible pretreatment for the top beam, shield beam, and front and rear rods. The numerical simulation model of four-leg hydraulic support is established with ADAMS, where variable stiffness spring is used to replace columns to simulate their elastic characteristics. Building on analysis of the specific parameters of the support, this paper attempts to study the adaptability of the hydraulic support with impact dynamic load acting on the top beam. Additionally, the impact coefficient I and the excitation coefficient E have been introduced to transform the analysis results and optimize the evaluation method of the response degree of the top beam under impact load. Consequently, the response characteristics of the columns and pins at the hinged joints under various coupling states of the surrounding rock are found. Meanwhile, the paper has made a detailed comparison on the stress state of hydraulic support with different impact loads acting on the top beam. The adaptability change rule of the impact dynamic load under various impact conditions has been explored, which is of great significance to the optimization and strength design of four-leg hydraulic support with large mining height.